Effects of anisotropic energetic particles on zonal flow residual level. (23rd July 2021) - Lu, Z.X.; Weiland, M.; Lauber, Ph.; Wang, X.; Meng, G.; Zonca, F.
Abstract: In tokamak plasmas, the interaction among the micro-turbulence, zonal flows (ZFs) and energetic particles (EPs) can affect the turbulence saturation level and the consequent confinement quality and thus, is important for future burning plasmas. In this work, the EP anisotropy effects on the ZF residual level are studied by using anisotropic EP distributions with dependence on pitch. Significant effects on the long wavelength ZFs have been found when small to moderate width around the dominant pitch in the EP distribution function is assumed. In addition, it is found that ZF residual level is enhanced by barely passing/trapped and/or deeply trapped EPs, but it is suppressed by well passing and/or intermediate trapped EPs. Numerical calculation shows that for ASDEX Upgrade plasmas, typical EP distribution functions can bring in −3% to +5.5% mitigation/enhancement in ZF residual level, depending on the EP distribution functions.